A educação ambiental nos encontros do congo com os cotidianos escolares de uma Escola Municipal da Barra do Jucu, Vila Velha, ES - Roldi, Ana Paula Dias Pazzaglini (2014)
The research “The Environmental Education in the Congo meeting with the routine in a local school in Barra do Jucu, Vila Velha, ES.” is about a narrative production in Environmental Education and the everyday things, White the intention of understanding some problems related to knowledge and enviroment things produced in the cultural meeting about congo and the school routine. With the conversations and narratives of the subjects of this research, students, teachers, "congueiros", students’ parents and others comunity representatives, we found the problem and identified the knowledge and things related to environment. We understood its diferent meanings. The school routine is considered a cheat space to cultural, environmental, social and curriculum hierarchies because these are privileged spaces to practice things that are not in the curriculum, and we emphasize what is around the school and the localspecifities that are nice for knowledge production and creation of a new curriculum everyday. The congo workshops that happen in an Elementary and Middle Public School in Barra do Jucu showed they are important to the development of the Environmental Education in a postcolonial view that believes in a possible thought that goes through the cultural/nature dichotomous and the not cultural homogeneization.The cultural productions developed in the workshops showed new alternatives to the production of subjective things, cultural and environmental knowledge exchange, based on the solidarity that means sustainable social acts.